AL-Hisbah Institution and its Development at Al-Andalus during the middle ages - صارم وفاء; مهنا أسامة; رجب وائل (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
Al- Hisbah is considered one of the important functions which regulate the society in the Islamic country. But is it a system that the Islam was created it, or it was existent before that? Could anyone hold Al- Hisbah functions or it is a certain conditions to take it? and how the Al- Hisbah system is developing in Al-Andalus under the Islamic culture during the middle ages? This research answered the previous questions, where the research studied al- hisbah as an integrand system to regulation Islamic society life at Al- Andalus during a number of dialogists. In the first dialogist we discuss theory of al- hisbah emergence and its development during the middle ages. Where, in the second, we talk about major qualifications and conditions that the situated on al- Muhtasib process have to possess them to can do his functions happily and command. Also, the research studied relationship between cogitations of al- hisbah and the judgment, and integrant their roles in regulation of Islamic society and conservation on its community during the middle ages.